THERMAL STRESS ANALYSIS OF OPTICAL FIBER IN FLEXIBLE PTOELECTRONIC INTERCONNECTION PRINTED CIRCUIT BOARD BASED ON FINITE ELEMENT METHOD - WANG WeiYin; WU ZhaoHua; CHEN GuDi; WANG ZhiQi; CHEN XiaoYong (Jixie qiangdu)
According to the influence of glass fiber embedded in flexible photoelectric printed circuit board received the thermal stress. The three-dimensional model of flexible photovoltaic substrate was established. Using the finite element thermodynamic analysis method,the comsol software was used to obtain the thermal stress value of the optical fiber in three kinds of groove structures including rectangular,U-shaped and trapezoidal under the SnAgCu lead-free solder reflow soldering process conditions. The results show that the maximum stress occurs at both ends of the optical fiber. When burying a glass fiber without coating layer,the U-shaped groove structure is suitable and the maximum thermal stress is 116. 8 MPa,which is the smallest one in the three kinds of structures. For coated glass fiber,the rectangular groove one is acceptable,and its maximum thermal stress is 100. 99 MPa; In three kinds of groove structures,the maximum position offset in three directions of XYZ is less than 1 μm.The research conclusion has certain reference value and guiding significance for designing the embedded structure of flexible optoelectronic printed circuit boards.